Proposed Learning and Development Plan for Pre-Service Teachers’ Community Engagement - Marc DG Garvida; Melvin O. Mortera; Imelda D. Sioson (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study explores the challenges pre-service teachers face in community engagement and develops a structured plan to enhance their readiness and effectiveness. The research identifies key barriers, including travel delays, limited resources, and coordination difficulties, which impact instructional time and quality. By converting these challenges into design inputs, the study proposes a learning and development plan integrating boot camps, micro-teaching, partnership projects, and learner-centered routines. The inclusion of Universal Design for Learning (UDL) and high-dosage tutoring frameworks supports inclusive pedagogy and equitable education. Recommendations emphasized targeted training, competency-based modules, supervision cycles, and institutional support to sustain community programs and improve pre-service teacher preparedness. The proposed learning and development plan helps pre-service teachers build key skills in planning, teaching, and coordination. Clear routines, shared calendars, and travel limits reduced delays and protected learning. Portable kits and learner-centered approaches kept instruction uninterrupted. Quick probes, coaching notes, and one-page handovers improved feedback and continuity across teams. Overall, communication with partners became smoother, and sessions were safer and more reliable across sites. This approach fosters stronger school-community partnerships and enhances adaptability in diverse educational settings. For policy recommendations, the Institution’s Student Sector Groups (Student Council, College of Education Council, Pre-service Teachers’ Association) may adopt an integrated system for implementing students’ community engagement activities, in coordination with the Extension and Community Services Office. Such an approach will foster more meaningful student participation and ensure sustainable, student-led community programs.